Hydrochemical characteristics and environmental evaluation of surface and groundwater quality at Al-Tarmiyah Area, Baghdad, Iraq - Ismael, Mustafa Haqi; Al-Tawash, Balsam Salim; Al-Saady, Younus I. (Iraqi Journal of Science, 2019)
The present study aims to assess the water quality and the hydrochemical characteristics and seasonal variation of surface water on the aspect of trace elements in Al-Tarmiyah District, Baghdad, Iraq. Ten water samples were collected, four from surface water and six from groundwater on October 2017, and on April 2018. All samples were analyzed for physiochemical parameters such as water temperature, pH, EC, TDS,TH,TSS, major ions (Ca2+, Mg2+, Na+, K+, SO42-, Cl-, and HCO3-), and nutrients (NO3-, and PO43-). In addition, samples were analyzed for trace elements that include Fe, Al, Pb, Zn, Mn, Cr, Cu, Co, Ni, and Cd. Suitability of water for domestic uses was evaluated depending on the criteria or standards of acceptable quality for that use. Surface water samples of October 2017 were classified as Ca-Cl and Na-Cl water type while they were classified as Na-Cl water type in April 2018. Most groundwater of both months’ samples was classified as Ca-Cl and Na-Cl water types. There is only one groundwater sample (GW2) was classified as Ca-SO4-2 water type. According to water classification based on the Piper diagram, most of surface and groundwater samples for both months falling in class (e), this means that the type of water is "Earth alkaline water with increased portions of alkalis with prevailing sulfate or chloride". Suitability of water for drinking purpose is evaluated depending on the criteria or standards of acceptable quality for that use ( WHO and Iraqi Standard). All surface and groundwater samples from the studied area are not suitable for drinking purposes and within "excellent typeâ€ for livestock and poultry use. Additionally, almost all surface water samples were within Good class based on the suggested limits of EC value (Ayers and Westcot, 1985) for irrigation while most of the groundwater samples are within unsuitable class. All surface water and groundwater samples lie within low hazard class of the irrigation water based on SAR values.